Customer Satisfaction of Students with Front-Line Service Delivery at a Private Higher Institution in Cavite, Philippines - Anit, Jannet (JPAIR Institutional Research, 2024)
This study investigates student satisfaction with frontline service delivery at San Sebastian College-Recoletos de Cavite (SSC-R), recognizing the critical role of service providers in enhancing student experiences. The primary aim is to assess the level of satisfaction among students, identify challenges faced by frontline staff, and evaluate existing support strategies to recommend evidence-based approaches for improvement. Employing a mixed-methods research design, the study combines descriptive and evaluative methods, utilizing an online survey questionnaire to gather data from senior high school and college students, as well as frontline service staff across ten service offices. The findings reveal that students generally express satisfaction with the quality of services, particularly in terms of timeliness, quality, efficiency, and adequacy. However, senior high school students reported higher satisfaction levels compared to their college counterparts. The study identifies significant challenges faced by frontline staff, including data fragmentation, diverse student needs, and a demanding work environment. In conclusion, the research highlights the necessity for targeted interventions to bridge the satisfaction gap, improve staff effectiveness, and foster a culture of continuous improvement, ultimately enhancing the overall student experience at SSC-R.
Keywords: Higher Education; frontline staff; frontline services; continuous improvement; satisfaction and academic outcomes; mixed-methods design; Philippines